Religious minorities, Islam, and the law - Khanif, Al, 1979- author.
1 online resource.
Keywords: This book examines the legal conundrum of reconciling international human rights law in a Muslim majority country and identifies a trajectory for negotiating the protection of religious minorities within Islam. The work explores the history of religious minorities within Islam in Indonesia, which contains the world's largest Muslim population, as well as the present-day ways by which the government may address issues through reconciling international human rights law and Islamic law. Given the context of multiple sets of religious norms in Indonesia, this is a complicated endeavour. In addition to amending and enacting human rights norms, the government is also negotiating with the long history of Islamisation in Indonesia. Particularly relevant is the practice of customary law, which puts the rights of community over individualism. This practice directly affects the rights of religious minorities within Islam. Readers, especially those conducting research, will also be provided with information and references which are relevant to the field of human rights, especiallyin relationtoreligious minorities and international law. The book will be a valuable resource for academics and researchers in the fields of International Human Rights Law, Law and Religion, and Islamic Studies.